An Effort to Monitor River Water Quality with Biomonitoring Method in Sumo River, Surabaya City - Setya, Mikhael Pratama Abdi; Revalandro, Gorin (Faculty of Civil Engeneering and Planning - ITATS, 2025)
River water quality has degradation due to anthropogenic activities in urban areas. It is requires an effective and sustainable monitoring approach. This study aims to evaluate the water quality of Sumo River, Surabaya, through biomonitoring method using macrozoobenthos indicators and physico-chemical parameters. Sampling was conducted in three segments (1, 2, and 3) by analyzing BOD, COD, pH, temperature, TDS, turbidity, and Shannon-Wiener diversity index (H'). Results denoted that BOD (13,4 – 33,23 mg/L) and COD (34,6 – 76,26 mg/L) values in all segments exceeded the class 3 quality standard, Appendix VI, PP No. 22 of 2021, with the highest pollution in segment 3. The parameters pH (7,6 – 7,76), temperature (29,5 – 29,6°C), and TDS (465 – 551 mg/L) still met the standard, but turbidity in segment 3 reached 16,39 NTU. Biological analysis revealed a decrease in macrozoobenthos diversity from segment 1 (H' = 1,0588) to segment 3 (H' = 0,5004), dominated by pollution-tolerant species such as Tubificidae. These findings reflect the severe ecological pressure due to the accumulation of domestic and industrial waste, especially in segment 3 with slow flow and poor waste management. This study recommends the implementation of an integrated sewage treatment system, increased community education, and periodic biomonitoring-based monitoring for the sustainable recovery of the Sumo River ecosystem, Surabaya City.